Improved Efficiency of Dye-Sensitized Solar Cells Based on a Double Layered TiO2 Photoanode - Ariyasinghe1, D.M.B.P.; Shimomura1, M. (Asian Journal of Chemistry, 2013)
A dye-sensitized solar cell (DSSC) consists of a TiO2 nanocrystalline photoanode, electrolyte and a counter electrode. In this work, spray pyrolysis deposition technique was used to construct the nanocrystalline TiO2 film. We found that repetitive spraying and sintering processes assists to decrease the number of cracks in the TiO2 film. The TiO2 electrodes were constructed by varying the bottom layer thickness with keeping total thickness of the film. The highest conversion efficiency of 8.5 % was obtained with the double-layered electrode (top layer: 6 μm, bottom layer: 9 μm). Short-circuit current was obviously improved from 10.51 mA/cm2 of the single-layered electrode (15 μm thick) to 15.37 mA/cm2 of this double-layered electrode.